Genotypic and phenotypic characterization of chikungunya virus of different genotypes from Malaysia - Sam, I.C.; Loong, S.K.; Michael, J.C.; Chua, C.L.; Sulaiman, W.Y.W.; Vythilingam, I.; Chan, S.Y.; Chiam, C.W.; Yeong, Y.S.; AbuBakar, Sazaly; Chan, Yoke Fun (Public Library of Science, 2012)
Background: Mosquito-borne Chikungunya virus (CHIKV) has recently re-emerged globally. The epidemic East/Central/South African (ECSA) strains have spread for the first time to Asia, which previously only had endemic Asian strains. In Malaysia, the ECSA strain caused an extensive nationwide outbreak in 2008, while the Asian strains only caused limited outbreaks prior to this. To gain insight into these observed epidemiological differences, we compared genotypic and phenotypic characteristics of CHIKV of Asian and ECSA genotypes isolated in Malaysia. Methods and Findings: CHIKV of Asian and ECSA genotypes were isolated from patients during outbreaks in Bagan Panchor in 2006, and Johor in 2008. Sequencing of the CHIKV strains revealed 96.8 amino acid similarity, including an unusual 7 residue deletion in the nsP3 protein of the Asian strain. CHIKV replication in cells and Aedes mosquitoes was measured by virus titration. There were no differences in mammalian cell lines. The ECSA strain reached significantly higher titres in Ae. albopictus cells (C6/36). Both CHIKV strains infected Ae. albopictus mosquitoes at a higher rate than Ae. aegypti, but when compared to each other, the ECSA strain had much higher midgut infection and replication, and salivary gland dissemination, while the Asian strain infected Ae. aegypti at higher rates. Conclusions: The greater ability of the ECSA strain to replicate in Ae. albopictus may explain why it spread far more quickly and extensively in humans in Malaysia than the Asian strain ever did, particularly in rural areas where Ae. albopictus predominates. Intergenotypic genetic differences were found at E1, E2, and nsP3 sites previously reported to be determinants of host adaptability in alphaviruses. Transmission of CHIKV in humans is influenced by virus strain and vector species, which has implications for regions with more than one circulating CHIKV genotype and Aedes species.